PEMBELAJARAN MUATAN LOKAL BAHASA SASAK DALAM MEMBUDAYAKAN BETEMUE (BERTAMU) DAN BEBASE (BERBAHASA) SISWA SD NEGERI 1 KEDIRI LOMBOK BARAT (LP2M IAI NURUL HAKIM, 2021)
This research aims to find out the impact of local Sasak language charge learning in betemue and bebase to cultivate students SDN 1 Kediri, West Lombok. With the sub issues to follow: (1) the concept of the cultural values of betemue and bebase in Sasak language local content learning (2) learing strategies local Sasak language charge in familiarizing the culture of betemue (3) local charge of language learning strategies in Sasak culture get used bebase (4) the impact of the local Sasak language charge learning in cultural betemue and bebase get used. The results showed that: the impact of local content of learning cultural betemue show results that are not significant. This is because 9 students did not understand the true betemue culture according to the custom of the Sasak, 4 students are less understood and 3 students who already understand and apply it in life. While the impact of cultural bebase in Sasak language local content learning is also very insignificant. Because of from 16 students grade 5, only 1 person students can use alus language by placing the appropriate strata allocation. This means that only 1 course students who can afford bebase and who can not afford 15 of 16 students